Analisis Waktu Pelaksanaan Kerja Pada Proyek Pembangunan Menara Lonceng Gereja Santo Martinus Bola Dengan Menggunakan Metode CPM (Critical Path Method) - Claudia Ekarista Sika Keytimu; Firnimus Konstantinus Bhara; Mariela Anjelica Natasya (Fakultas Teknik Universitas Khairun, 2026)
This studi aims to analyze the scheduling of the Ball Tower Construction Project of Santo. Martinus Bola Church using the Critical Path Method (CPM) to determine the critical path method. and estimate the optimal project completion time. The research data were obtained fro the project’s activity breakdown and analyzed using forward pass and backward pass calculations to determine the earliest start(ES), earliest finish (EF), latest start(LS), latest finish (LF), and slack time for each activity. This analysis results show that there are 16 activities included in the critical path, such as hard soil excavation for footplate foundations, sand backfill under the footplate, and reinforced concrete structural works from sloof, columns, beams, to floor slabs and roof slabs. Meanwhile, 4 other activities are non-critical as they shortened from the initial plan of 215 days, resulting in an acceleration of 35 days. These findings indicate that the CPM is effective for planning and controlling project time in building construction projects.